2011
DOI: 10.1111/j.1365-2036.2011.04860.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sorafenib in hepatocellular carcinoma: the impact of the Child-Pugh score

Abstract: SUMMARY BackgroundSorafenib increases median survival and time to radiological progression in patients with advanced hepatocellular carcinoma, but its benefit for ChildPugh B patients remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 29 publications
7
95
3
3
Order By: Relevance
“…Therefore, it is important to establish predictive factors for sorafenib therapy. Previous studies demonstrated that several factors, such as Eastern Cooperative Oncology Group PS and CP class A status were predictive factors for patients with HCC receiving sorafenib therapy (11,12). In recent reports, skeletal muscle mass loss was found to be significantly associated with malnutrition and poor liver function (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to establish predictive factors for sorafenib therapy. Previous studies demonstrated that several factors, such as Eastern Cooperative Oncology Group PS and CP class A status were predictive factors for patients with HCC receiving sorafenib therapy (11,12). In recent reports, skeletal muscle mass loss was found to be significantly associated with malnutrition and poor liver function (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…An additional finding was the 8.1-month median OS of the five Child-Pugh B patients. Previous experience with comparable patient populations has shown an OS for Child Pugh B patients in the range of 3.5-5.5 months [1][2][3]. Considering that Child Pugh B patients treated with sorafenib generally have poor outcomes due to underlying liver dysfunction, CF102 also may be considered as a drug to be developed for this patient sub-population.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS for Child-Pugh A patients was 41 weeks and for Child-Pugh B patients 14 weeks (7). Several studies also demonstrated that Child-Pugh B patients fare worse compared with Child-Pugh A patients and also present with worsening of cirrhosis more frequently during treatment (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%